Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s12008-014-0231-6
|View full text |Cite
|
Sign up to set email alerts
|

IDGL, an interaction design framework based on systematic innovation and quality function deployment

Abstract: Concerns about human-machine interaction are becoming one of the most important thrusts for the development of innovative and successful products. Interaction design methods and tools are already described in literature and available for designers, and the analysis of their characteristics suggests the synergy with other research fields aimed at developing an interaction design framework as complete as possible. The complementary aspects of the inventive problem solving theory named TRIZ were considered, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…This study suggests that additional pillars should be constructed based on the following groups: 1) Validation of the product's requirements: This pillar should contain all the methods that are aiming to validate the correctness of the decisions that translate the customer needs into product characteristics and later specifications. Methods such QFD, TRIZ, AHP and other similar methods are able to provide a robust approach on which Key Characteristics (KCs) will be defined for the product and link the selection of those KCs with the users' expectations (Chin, Zheng and Wei, 2003;Filippi and Barattin, 2016). Other methods in later stages will be able to provide guidelines on how and which of those KCs will be transformed into Key Control Characteristics (KCCs) during the manufacturing stage.…”
Section: Verification and Validation Pillars For Plm Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggests that additional pillars should be constructed based on the following groups: 1) Validation of the product's requirements: This pillar should contain all the methods that are aiming to validate the correctness of the decisions that translate the customer needs into product characteristics and later specifications. Methods such QFD, TRIZ, AHP and other similar methods are able to provide a robust approach on which Key Characteristics (KCs) will be defined for the product and link the selection of those KCs with the users' expectations (Chin, Zheng and Wei, 2003;Filippi and Barattin, 2016). Other methods in later stages will be able to provide guidelines on how and which of those KCs will be transformed into Key Control Characteristics (KCCs) during the manufacturing stage.…”
Section: Verification and Validation Pillars For Plm Approachmentioning
confidence: 99%
“…Modern manufacturing is struggling to cope with globalisation, product customisation and the continuously decreasing time to market (Maropoulos and Ceglarek, 2010;Filippi and Barattin, 2016). Practices that promote the 'make it correct the first time' approach are becoming increasingly important, especially in product design, which can be an extremely timeconsuming process .…”
Section: Introductionmentioning
confidence: 99%
“…It is a "solution concept" that still has to be validated. Filippi and Daniela [19], showed that TRIZ aspects can be completed with other methods like quality function deployment (GFD) to have an interaction design guide.…”
Section: The Triz Inventive Approachmentioning
confidence: 99%
“…Otherwise, products are not acceptable even though they are of well-designed and -developed [11]. e focus of product innovation has been shifting from technology to user experience and HCI in that sense [12].…”
Section: Introductionmentioning
confidence: 99%